3D PRINTING DAN MEDIA PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Luthfi Hamdani Maula (Jurnal Pesona Dasar, 2019)
This study aims to describe 3D printing as a medium of mathematics learning for students in the context of prospective teacher learning in accordance with the increasingly rapid technological development. Consideration in this study is that many teachers find it difficult in learning media both in making and developing learning media. 3D printing is one solution that can be offered by technology in order to solve the problems experienced by teachers. This research was conducted with a descriptive qualitative method with PGSD students participating in mathematics concentration at the University of Muhammadiyah Sukabumi totalling 20 people. Based on the results of this study, students can operate and print mathematics learning media through 3D printing. In addition to making media for learning, 3D printing also sharpens digital literacy for students to prepare teachers for the future.